The millipede genus Plusioglyphiulus Silvestri, 1923 in Thailand (Diplopoda, Spirostreptida, Cambalopsidae) - Golovatch, Sergei I.; Geoffroy, Jean-Jacques; Mauriès, Jean-Paul; Vandenspiegel, Didier (Zootaxa, 2011)
The basically southeast Asian genus Plusioglyphiulus is shown to currently comprise 27 species, all keyed, of which 13 are new, stemming from Thailand, and mapped: P. panhai sp. n., P. antiquior sp. n., P. sutchariti sp. n., P. likhitrakarni sp. n., P. pimvichaiae sp. n., P. erawan sp. n., P. wat sp. n., P. tham sp. n., P. phra sp. n., P. jaydee sp. n., P. puttakun sp. n., P. saksit sp. n. and P. samakkee sp. n. Although the new species have mainly been collected in caves, none seems to actually represent a troglobiont. A second record of P. ampullifer Golovatch, Geoffroy, Mauriès & VandenSpiegel, 2009 is provided in southern Vietnam, as well as new illustrations are presented for P. bessoni Golovatch, Geoffroy, Mauriès & VandenSpiegel, 2009, prepared from strictly topotypic samples in northern Thailand. With the discovery of P. panhai sp. n. and, especially, P. antiquior sp. n., both from southern Thailand, and both markedly transitional to the more northerly diversified javanicus-group of Glyphiulus, the genus Plusioglyphiulus is reconfirmed as being heterogeneous. Its diagnosis seems to be based now only on a single, rather weak apomorphy in posterior gonopod structure. Some evolutionary and zoogeographical considerations are presented to substantiate the predominantly eastward and/or southward speciation events in typical Plusioglyphiulus which have reached northern and eastern Borneo in the east and southeast.